A multivariate twin study of the genetic association between mindfulness and subjective well-being - Morgan Driver; Danielle Dick; Thalia C Eley; Sally I Kuo; Kirk Warren Brown; Fazil Aliev (OSF Registries, 2021)
Considerable research (e.g., Brown, 2015; Quaglia et al., 2016) shows that mindfulness, a receptive attention to present events and experiences (Analayo, 2003; Brown & Ryan, 2003), is phenotypically correlated to subjective well-being (SWB), commonly regarded as higher life satisfaction along with a preponderence of positive over negative affect (Diener, 1984; 2000). Unknown is why the relation between these two dispositions exists. Intrapsychic phenomena have been invoked to explain their relation (e.g., Brown et al., 2007; Holzel et al., 2011), but indirect evidence suggests that they may hare genetic overlap. Specifically, research drawing from the TEDS dataset showed that mindfulness had genetic overlap with internalizing symptoms (depression and anxiety sensitivity; Waszczuk et al., 2015), and these symptoms are inversely correlated with SWB. Substantial heritability has been found for both mindfulness (Siebelink et et al., 2019; Waszczuk et al., 2015) and SWB (e.g., Haworth et al, 2017; Roysamb et al., 2018) and the present proposal seeks to understand what proportion of the variance in the phenotypic association between them is explained by genetic influence, relative to shared and nonshared environmental influence.
Keywords: Social and Behavioral Sciences; Psychology